Konsep Mendidik Anak secara Islami dalam Hadits Rosulullah Saw Berdasarkan Buku Karya DR. Muhammad Nur Abdul Hafizh Suwaid dan Penerapannya di Masa Pandemi - Nita Nuryuliastuti; Mujiburrohman Mujiburrohman; Iffah Mukhlisah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
In modern times we are experiencing a change of era, In these changes, there have been many incidents of moral and moral decline. This concept aims to be an additional insight and also aims as a reference for educating parents. This type of research is library research or literature (Library Research). The focus of scientific studies on literature that is relevant to the research theme and the main reference is in the book Prophetic Parenting by Dr. Muhammad Nur Abdul Hafizh Suwaid. The results of this study Parents can know how the concept of educating children is Islamic and Knowing activities to apply the concept of educating children in an Islamic way comes from the Hadith of the Prophet Muhammad and the Qur'an.